The Impact of Fiscal and Monetary Shock on Economic Activity in Serbia: SVAR Approach - Bungin, Sanja (Industrija, 2017)
Contribution of fiscal policy to macroeconomic stabilization is significant. The main objective of this article is to assess the impact of fiscal and monetary shock to macroeconomic variables in Serbia in period between the years 2007-2016.This period covers the implementation of inflation targeting strategy in Serbia with the main goal of monetary policy is price stability. One of the biggest concerns in inflation targeting framework is fiscal discipline. In research is implemented structural vector autoregression. The results showed that both fiscal and monetary shocks affect Serbian economy.